Architecture des logiciels et langages de modelisation - Breitkopf, Piotr; Touzot, Gilbert (European Journal of Computational Mechanics, 1992)
The article points out major difficulties emerging in the software developement for computational engineering purposes. Solutions are suggesteed, some of them are not definitive. The common characteritics of existing programs are described ; the problems encountered are detailed. Finally the solutions adopted for the SIC program general architecture are presented. SIC is developed at UTC, since 1985 in cooperation with industry partners and scientific laboratories from Marseille, Grenoble, Montpellier, Poitiers.